Design of very‐low‐profile circular UHF small antenna using characteristic mode analysis. Issue 8 (19th May 2017) - Gao, Yue; Ma, Runbo; Zhang, Qianyun; Parini, Clive
Abstract : This study presents a very‐low‐profile circular ultra‐high frequency (UHF) small antenna with a radiating body transformed from a monopole. The proposed radiating body is gradually improved by analysing fundamental modes of the structure with different ground planes via characteristic mode analysis (CMA). CMAs demonstrate operating principles of the radiating body so that a magnetic feeding loop is proposed to excite the radiating body. An equivalent circuit of the radiating body and magnetic feeding loop is then established. The relationships between antenna bandwidth, and eigen value and modal significance are derived through physical insight of the CMA. A prototype of the proposed circular antenna operating at 474 MHz is fabricated and measured. It has a radius of 5.2%λ c (λ c is the operating wavelength), and a profile of 5.2%λ c The CMA of the proposed antenna with testing cable at different lengths is applied to understand the discrepancy between simulations and measurements. The analysis and performance evaluation shows that the proposed antenna can be a strong contender for compact sensors for machine‐to‐machine and internet of things applications.